Gait risk factors for disease progression differ between non-traumatic and post-traumatic knee osteoarthritis. Issue 11 (November 2021) - Robbins, S.M.; Pelletier, J.-P.; Abram, F.; Boily, M.; Antoniou, J.; Martineau, P.A.; Morelli, M.; Martel-Pelletier, J.
Summary: Objective: To examine if relationships between knee osteoarthritis (OA) progression with knee moments and muscle activation during gait vary between patients with non-traumatic and post-traumatic knee OA. Design: This longitudinal study included participants with non-traumatic ( n  = 17) and post-traumatic ( n  = 18) knee OA; the latter group had a previous anterior cruciate ligament rupture. Motion capture cameras, force plates, and surface electromyography measured knee moments and lower extremity muscle activation during gait. Cartilage volume change were determined over 2 years using magnetic resonance imaging in four regions: medial and lateral plateau and condyle. Linear regression analysis examined relationships between cartilage change with gait metrics (moments, muscle activation), group, and their interaction. Results: Measures from knee adduction and rotation moments were related to lateral condyle cartilage loss in both groups, and knee adduction moment to lateral plateau cartilage loss in the non-traumatic group only [ β  = −1.336, 95% confidence intervals (CI) = -2.653 to −0.019]. Generally, lower levels of stance phase muscle activation were related to greater cartilage loss. The relationship between cartilage loss in some regions with muscle activation characteristics varied between non-traumatic and post-traumatic groups including for: lateral hamstring (lateral condyle β  = 0.128, 95%CI = 0.003 to 0.253; medial plateau β  = 0.199, 95%CI = 0.059 to 0.339), rectus femoris (medial condyle β  = −0.267, 95%CI = −0.460 to −0.073), and medial hamstrings (medial plateau; β  = −0.146, 95%CI = −0.244 to −0.048). Conclusion: Findings indicate that gait risk factors for OA progression may vary between patients with non-traumatic and post-traumatic knee OA. These OA subtypes should be considered in studies that investigate gait metrics as risk factors for OA progression.